1995
DOI: 10.1111/j.1151-2916.1995.tb08362.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Properties of Ln‐Si‐O‐N Glasses (Ln = Lanthanides or Y)

Abstract: Homogeneous Y‐Si‐O‐N glasses containing 15 or 20 eq% nitrogen (N) were prepared from compositions with Y/Si ratios in the vicinity of that of the lowest eutectic point on the Y2O3–SiO2 phase diagram. The liquidus on the phase diagram shifted toward lower temperatures by incorporation of N. The density, the elastic moduli, and the glass transition temperature of the Y‐Si‐O‐N glasses increased with incorporation of N. This is due to the closer packing of atoms in the glasses by the substitution of N, which is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
106
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 18 publications
13
106
0
2
Order By: Relevance
“…The fact that ionic radius (and CFS) of Y lies between radii of Gd and Yb seems to be a coincidence. Thus, although hardness and some other properties of Y-glasses often fit the dependence on CFS for lanthanide-containing glasses, 13,15,17,19 Y belong into another group together with Sc. There are some experimental data supporting this conclusion.…”
Section: Density Vs Hardnessmentioning
confidence: 95%
See 1 more Smart Citation
“…The fact that ionic radius (and CFS) of Y lies between radii of Gd and Yb seems to be a coincidence. Thus, although hardness and some other properties of Y-glasses often fit the dependence on CFS for lanthanide-containing glasses, 13,15,17,19 Y belong into another group together with Sc. There are some experimental data supporting this conclusion.…”
Section: Density Vs Hardnessmentioning
confidence: 95%
“…2À7,11,12 Because of higher valence of nitrogen, partial substitution of oxygen by nitrogen in the network produces tighter and more linked structure. It results in linear increase in density, 4,10,13À17 hardness, 3,4,8,9,15,17 Young's modulus, 8,13,16À18 thermal expansion coefficient, 4,6,9,13,19,20 glass transition temperature, 4,6,9,13,19,20 viscosity 9,14,15,21 etc. For instance, adding 20 eq.% of N resulted in 33% increase in La-and 23% increase of elastic modulus in Lu-containing oxynitride glasses.…”
Section: Introductionmentioning
confidence: 97%
“…[2][3][4] A number of investigations have been carried out on bulk glass formation and properties in several M-Si-O-N and M-Si-Al-O-N systems where M is a modifying cation such as the alkaline earths (Mg, Ca, Ba) [5][6][7][8][9] or Y 5-7,10-15 and the rare earth lanthanides. [16][17][18][19][20][21][22][23][24] The first systematic studies 5,6,11 on the effect of replacing oxygen by nitrogen in oxynitride glasses reported that for all Mg-, Ca-, Y-and Nd-Si-Al-O-N glasses with constant cation ratios, incorporation of nitrogen resulted in increases in glass transition temperature (T g ), viscosity, hardness, refractive index, dielectric constant and ac conductivity. Viscosity increases by more than two orders of magnitude simply by replacing 18 e/o oxygen by nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…This causes substantial variations in the various properties (softening point, 12) glass transition temperature, [12][13][14][15][16][17][18][19] liquidus temperature, [20][21][22] elasticity modulus, 23) refractive index, 13,18,23) expansion coefficient, [13][14][15][16][17] hardness, Fumiyuki SHIMIZU, 1) Hirofumi TOKUNAGA, 2) Noritaka SAITO 2) and Kunihiko NAKASHIMA 2) 1) Production Department, Shoei Chemical Inc., 5-3, Aza-wakazakura, Fujinoki-machi, Tosu 841-0048 Japan. ).…”
Section: )mentioning
confidence: 99%
“…
15,17,24,25) shear modulus, 12,14) Young's modulus 12,14,16) and density 14,15,17) ) of rare-earth containing oxide and/or oxynitride glasses that are the grain boundary phase of Si 3 N 4 ceramics sintered with rare-earth oxide additives, and thus, can also affect grain growth of b-Si 3 N 4 itself. However, to our best knowledge, there are no available data on the physical properties of rare-earth containing high temperature melts.
…”
mentioning
confidence: 99%